2011
DOI: 10.1159/000330740
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Ondansetron Decreases the Analgesic Efficacy of Tramadol in Humans

Abstract: Tramadol, a central analgesic acting on serotonin neurotransmission, is often co-used with ondansetron, a 5-HT3 antagonist, for the management of postoperative pain to decrease nausea and vomiting. The aim of the study is to test the hypothesis that this drug combination raises tramadol requirement by patient-controlled analgesia (PCA). Forty patients undergoing hernioplasty or thyroidectomy were enrolled in a randomized, controlled study and allocated to receive ondansetron 4 mg i.v. (n = 20) or sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…We were unable to perform any meaningful meta-analysis of nausea or vomiting for this study as the outcome was reported inconsistently with different measures and at different time points. Although some studies [4,6] supported the suggestion of an increased incidence of nausea when ondansetron was co-administered with tramadol, the finding was not confirmed among the remainder [5,[7][8][9]11]. Whether or not the co-administration of ondansetron and tramadol results in a higher incidence of nausea and/or vomiting, and if so, whether this is due to a direct effect on the efficacy of ondansetron or secondary to increased tramadol consumption, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were unable to perform any meaningful meta-analysis of nausea or vomiting for this study as the outcome was reported inconsistently with different measures and at different time points. Although some studies [4,6] supported the suggestion of an increased incidence of nausea when ondansetron was co-administered with tramadol, the finding was not confirmed among the remainder [5,[7][8][9]11]. Whether or not the co-administration of ondansetron and tramadol results in a higher incidence of nausea and/or vomiting, and if so, whether this is due to a direct effect on the efficacy of ondansetron or secondary to increased tramadol consumption, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Where numerical values of mean and SD results of cumulative tramadol consumption were not supplied within published papers, the author, where available, was contacted by email. Where the information was still not obtained [7][8][9], enlarged-scale visual estimation of the data was undertaken using the figures in the published studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that the nausea and vomiting associated with the use of tramadol has high incidence [6,7]. The low dose naloxone infusion, transcutaneous electrical acupuncture point stimulation, ondansetron were preferred until today in the treatment of tramadol induced nausea and vomiting (TINV) [8][9][10]. However, there are publications suggest to that ondansetron may reduce the analgesic effect of tramadol.…”
Section: Introductionmentioning
confidence: 99%
“…A ondansetrona tem sido identificada como causa de significante redução da ação de ciclofosfamida e cisplatina. Estudos mais recentes mostram que o uso concomitante do antagonista serotoninérgico com os analgésicos opióides pode reduzir o controle álgico, explicado pelo fato de a parcela da ação dos opióides sobre a dor ocorrer via receptor 5-HT (Vale et al, 2011).…”
Section: Interação Medicamentosaunclassified